The impact of underrepresentation in cardiovascular trials on minorities in the United States - Lombardi, Federica (Open Science Journal, 2022)
In the United States a great underrepresentation of minorities in cardiovascular trials was registered. This brings a lot of harm to their health because underrepresentation does not give them the possibility to develop the right knowledge to treat them in the best way possible. In addition, minorities in the United States are more likely to have a low socioeconomic status and not be able to afford health insurance and access care. This issue leads to minorities having higher Cardiovascular Disease mortality and risk factors rates than White people. Disorders like Hypertension, Hypercholesterolemia, Obesity, and Diabetes are more prevalent among minorities especially because of their low socioeconomic status and less access to continuous care. Over the past years, the situation was tried to improve, but without any success. Despite the approval of guidelines, many researchers do not even report the patients’ races, not allowing them to have a vivid portrait of the situation. Economic reasons prevent researchers from recruiting minorities and mainly psychosocial factors, like mistrust or fear, and racism do not encourage minorities to participate in trials. Many can be the solutions for these problems, from investing more money to giving remunerations to participants. Furthermore, new and more inclusive recruitment strategies are needed, like the use of social media platforms. A rapid change is extremely necessary. Minorities are growing fast and many of them are not insured, have no access to primary care, and are more likely to die from Cardiovascular Disease.